2023
DOI: 10.2147/copd.s423148
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Benefits of Smoking Cessation Improve Respiratory Function and Metabolism in Smokers

Aldo Pezzuto,
Alberto Ricci,
Michela D'Ascanio
et al.

Abstract: Background Cigarette smoke exposure is the main preventable cause of chronic obstructive pulmonary disease (COPD). Airflow limitation is closely associated with smoking exposure. Smoking could also interfere with lipid metabolism. Aim To determine the respiratory functional and metabolic changes after smoking cessation in smokers in the short term. Methods All patients were current smokers. They were assessed by spirometry and questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“… 31 , 32 Furthermore, Pezzuto et al indicate that even one month of short-term smoking cessation improved lung function and cholesterol levels, which corroborates our results of smokers exhibiting worse survival on respiratory or cardiovascular disease. 33 Furthermore, we revealed that nonsmokers with COPD demonstrated a lower risk of all-cause mortality than smokers without COPD. Smoking itself exhibits a significant impact on mortality, 34 thus, smokers without COPD had a higher risk than nonsmokers with COPD.…”
Section: Discussionmentioning
confidence: 88%
“… 31 , 32 Furthermore, Pezzuto et al indicate that even one month of short-term smoking cessation improved lung function and cholesterol levels, which corroborates our results of smokers exhibiting worse survival on respiratory or cardiovascular disease. 33 Furthermore, we revealed that nonsmokers with COPD demonstrated a lower risk of all-cause mortality than smokers without COPD. Smoking itself exhibits a significant impact on mortality, 34 thus, smokers without COPD had a higher risk than nonsmokers with COPD.…”
Section: Discussionmentioning
confidence: 88%
“…A cohort study of 120 clients was conducted from April to December 2021 examining results of respiratory function and lipids following a smoking cessation program. 32 Study results showed a statistically significant decrease in TC (P < .001) and increase in HDL (P < .02) after only one month of cessation. Although these studies had small samples, these results are promising for improvement in lipid profiles soon after smoking cessation.…”
Section: Smoking Cessationmentioning
confidence: 86%
“…Additionally, the analysis did not take tobacco use into account, which can be an important factor in the pathophysiology of ILD. Therefore, tobacco cessation should always be recommended for these patients [28,29].…”
Section: Discussionmentioning
confidence: 99%